SISTEM MONITORING TRUK KELAPA SAWIT MENGGUNAKAN GPS TRACKING BERBASIS WEBSITE - Andri Nofiar Am; Antoni Pribadi; Fitri Fitri (Jurnal Pendidikan Teknologi Informasi (JUKANTI), 2022)
Transport vehicles in the form of trucks are one of the important components in supporting the logistics system when collecting crops in a plantation company. Fresh fruit bunches (FFB) produced by oil palm plantations must be sent to the location of the crude palm oil (CPO) processing plant at a predetermined time so that fruit quality is maintained. Therefore, scheduling and arranging the route of truck trips plays an important role. Constraints faced in plantations are the absence of a cellular internet network in plantations and limited road infrastructure so that location, time and route data cannot be accurately monitored. Scheduling can be done optimally and can reduce waiting times and queues of trucks that want to enter the shelter location. To overcome this problem, a monitoring system for oil palm trucks was created using a website-based GPS tracking. The components used are GPS Neo-6M, NodeMCU ESP8266, GSM SIM800L. It can be concluded that the tool can display data and information as expected, and the tool works well and can control the coordinates of the oil palm truck remotely.